Investigation of Factors Affecting Farmers' Attitude toward Sustainable Management of Agricultural Water Resources (Case Study: Wheat Farmers in Maragheh County) - Asma Eidi (University of Tabriz, 2021)
Abstract Background & Objective: The primary purpose of this study was to investigate the factors affecting farmers' attitudes towards sustainable management of agricultural water resources.